Meta-analisis tesis pengembangan bahan ajar fisika sekolah menengah menggunakan model inquiry based learning (IBL) untuk meningkatkan kompetensi peserta didik - Fitrah Ayu; Festiyed Festiyed; Djusmaini Djamas (Universitas Negeri Padang, 2019)
The research aims to determine the effect of the use of inquiry based learning model the development of high school physic learning material to increase student competences. The effect will be study from the previous researches. This research used meta-analysis method. Meta-analysis is the study on a number of research results in similar problem. The analysis unit in this research was written documents about the research of high school physic learning material using inquiry based learning model to increase the student competences, these were ten thesis which was taken purposively based on the compatibility with research theme. The main instrument of this research was self-research assisted by documentations guide. The data analysis that was used were qualitative data analysis for the data analysis for the data of narrative result toward the researches which was found and quantitative data with percentage value. The research result indicated hat high school physics learning material using inquiry based learning model is valid, practice, effective, and able to increase the students competences